Circulating levels of cytokines and risk of inflammatory bowel disease: evidence from genetic data - Liu, Bin; Qian, Yu; Li, Yanan; Shen, Xiangting; Ye, Ding; Mao, Yingying; Sun, Xiaohui (Frontiers in Immunology, 2023)
Background: Prior epidemiological studies have established a correlation between inflammatory cytokines and inflammatory bowel disease (IBD). However, the nature of this relationship remains uncertain. Mendelian randomization (MR) study has the advantages of avoiding confounding and reverse causality compared with traditional observational research.Objective: We aimed to evaluate whether genetically determined circulating levels of cytokines are associated with the risk of IBD by using the MR approach.We selected genetic variants associated with circulating levels of 28 cytokines at the genome-wide significance level from a genome-wide association study (GWAS) including 8,293 individuals. Summary-level data for IBD (including Crohn's disease and ulcerative colitis) were obtained from the International Inflammatory Bowel Disease Genetics Consortium and UK Biobank. We performed the primary analysis using the inverse-variance weighted method, as well as sensitivity analyses to test the stability of our results. We subsequently replicated the results of IBD in the UK Biobank dataset. A reverse MR analysis was also conducted to evaluate the possibility of reverse causation.Results: Genetically predicted elevated levels of interleukin-17 (IL-17) and monokine induced by interferon-gamma (MIG) were associated with an increased risk of IBD[odds ratio (OR): 1.52, 95% confidence interval (CI):1.10-2.08, P =0.010 for IL-17 and OR: 1.58, 95% CI: 1.24-2.00, P = 1.60×10 -4 for MIG]. Moreover, we observed a suggestive association between β-NGF and MIP-1β with the risk of Crohn's disease (OR: 0.71, 95% CI: 0.52-0.98, P = 0.039) and ulcerative colitis (OR:1.08, 95% CI: 1.01-1.15, P= 0.019). In the reverse MR study, there was no evidence of causal effects of IBD and these cytokines.Our study suggests the potential causal associations of IL-17 and MIG with IBD. Further studies are needed to determine whether IL-17 and MIG or their downstream effectors could be useful in the management of IBD.